(untitled) (Bangladesh Journal of Medical Science, 2019)
Background: The prevalence of Helicobacter pylori-related diseases varies geographically and it is partially determined by the virulence of the circulating strains. Cuba and Chile exhibit different gastric cancer rates, on despite of very similar H. pylori infection rates. We determined if differences in the pathogenic potential of H. pylori isolates from Chile and Cuba could explain the disease outcome in each population. Methods: H. pylori isolates from 78 Chilean and 71 Cuban patients were analyzed using PCR for the presence of cagA, babA2, vacA alleles and the pattern of EPIYA motifs. Results: cagA was detected in 94.9 % of Chilean and 64.7 % of Cuban isolates (P < 0.001) and was significantly associated with duodenal ulcer (DU) in Cuba (P < 0.01) but not in Chile. The presence of cagA with multiple EPIYA-C motifs was 18.2 % higher in Chile than in Cuba (P < 0.05). Also, an association was observed between GU (P ≤ 0.05) and premalignant lesions (P < 0.001) with the multiple EPIYA-C motif status of the strains in Chile, but not in Cuba. The prevalence of vacA s2m2 genotype was predominant in Chile (66.7 %), while in Cuba was prevalent the s1m1 genotype (56.8 %); and the last one was significantly associated with the presence of DU in Cuban patients. Conclusions: The cagA status and the EPIYA pattern found in Chilean and Cuban H. pylori clinical isolates partially explain the differences in disease prevalence between both countries. The high proportion of vacA s2m2 genotype in Chile was an unexpected result, needing further studies. Bangladesh Journal of Medical Science Vol.18(3) 2019 p.577-585